2012
DOI: 10.5812/jjm.4616
|View full text |Cite
|
Sign up to set email alerts
|

Prophage Typing of Methicillin Resistant Staphylococcus aureus Isolated from a Tertiary Care Hospital in Tehran, Iran

Abstract: This study has highlighted the presence of bacteriophage types among MRSA isolates to show the high potential of these isolates to produce broad spectrum of virulence factors. Background:Staphylococcus aureus is a common cause of infections among humans and animals and it is known as a community-acquired and nosocomial pathogen. Most of the isolates contain lysogenic phages which are responsible for production of various virulence factors such as enterotoxins, staphylokinase, β-lysin, lipase, exfoliative toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
5
18
3
Order By: Relevance
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38). Moreover, resistance of biofilmproducing strains to 13 tested antibiotics in this study highlighted the important role of these strains to cause severe infections, which do not respond to broad spectrum of antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38). Moreover, resistance of biofilmproducing strains to 13 tested antibiotics in this study highlighted the important role of these strains to cause severe infections, which do not respond to broad spectrum of antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…Comparing these two methods, the sensitivity of the phenotypic method with cefoxitin discs is relatively lower than with the genotypic method of mecA gene identification. However, even with the former method, the frequency of MRSA strains in this study was determined to be 35.8%, which is comparable to the rate found by other investigators in Iran (18,19). Nevertheless, this amount, compared to the results of previous studies, with a prevalence 80% in Tabriz (20), is different.…”
Section: Discussionsupporting
confidence: 69%
“…In other studies from Iran, the prevalence of penicillin resistance among MRSA isolates was 100% (10,(26)(27)(28)30). Possibly, the general use of ampicillin for the treatment of infections in poultry may explain this finding.…”
Section: Discussionmentioning
confidence: 78%
“…The occurrence of erythromycin resistance among poultry MRSA was significantly lower than that observed among MRSA of human origin, in Iran (10,(26)(27)(28)(29). Macrolides are not normally used for therapy of infections in poultry in Denmark, whereas the frequent occurrence of macrolide resistance might reflect the use of the spiramycin, as a growth promoter of poultry, in Iran.…”
Section: Discussionmentioning
confidence: 90%